2020
DOI: 10.1111/jdv.16637
|View full text |Cite
|
Sign up to set email alerts
|

Pictorial Representation of Illness and Self‐Measure to assess the perceived burden in patients with chronic inflammatory vulvar diseases: an observational study

Abstract: Background Chronic inflammatory vulvar diseases can have a huge detrimental impact on patient welfare. A few studies have addressed this issue so far, mainly measuring patients' quality of life or sexual dysfunction. Objective To assess the burden of suffering in patients with chronic inflammatory vulvar diseases using the Pictorial Representation of Illness and Self-Measure (PRISM), a visual, non-verbal instrument. We also assessed (i) the concordance between PRISM and the Dermatology Life Quality Index (DLQI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…A first expected result of our study was the great efficacy of a topical potent corticosteroid, like MMF, in improving both symptoms and clinical signs of VLS ( Table 2) and DLQI median score decreased from 6 [3][4][5][6][7][8] to 2 [1][2][3][4][5] (P < .0001). It was particularly interesting that PRISM and DLQI sores showed greater coefficients of variation when compared with those referred to global symptoms (GSS), objective features (GOS) and dyspareunia (Table 3).…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…A first expected result of our study was the great efficacy of a topical potent corticosteroid, like MMF, in improving both symptoms and clinical signs of VLS ( Table 2) and DLQI median score decreased from 6 [3][4][5][6][7][8] to 2 [1][2][3][4][5] (P < .0001). It was particularly interesting that PRISM and DLQI sores showed greater coefficients of variation when compared with those referred to global symptoms (GSS), objective features (GOS) and dyspareunia (Table 3).…”
Section: Discussionmentioning
confidence: 83%
“…This finding indicates that PRISM may be more reliable than DLQI in capturing the changes in disease-related burden after treatment as well as it appeared in quantifying the baseline burden. 6 Linear regression analysis showed that the global subjective…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations